Conversion-Associated Recombination in Yeast - Hurst, Donald D. (1972)
Gene conversion and conversion-associated reciprocal recombination have been studied in various Saccharomyces cerevisiae hybrids. In a sample of 11,023 unselected meiotic tetrads, 907 conversions were observed at the arg4, thr3, his1, and SUP6 loci. Of these conversions, 445 (or 49.1%) were associated with reciprocal recombination of bracketing markers no more than 20-centimorgans apart. For conversions of two other loci, his2 and thr1, for which the bracketing markers were more than 20-centimorgans apart, recombination frequencies were significantly greater than 50%. These findings are discussed in terms of current models of genetic recombination. It is suggested that all meiotic crossing-over is characterized by the recombination events that are associated with conversion.